1962
DOI: 10.1084/jem.115.2.439
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Epidermal Cells in Vitro by Autologous Serum From Normal Animals

Abstract: Although normal serum is sometimes said to be toxic to autologous cells in vitro (1), to our knowledge, data of such autotoxic effects have been previously reported only for spermatozoa (2, 3). Indeed, autologous serum is often used as the best nutrient medium for cells (4). Evidence will be presented here that fresh normal sera from rabbits and rats are lethal in vitro to autologous epidermal cells. In the test system employed, 70 to 100 per cent of epidermal cells were killed within 2 hours at 37°C. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1965
1965
1975
1975

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Both NHS and IMS produced lysis of murine thymocytes. This ob servation was in agreement with studies by other investigators, which demonstrated the cytotoxicity of heterologous sera for murine thymo cytes [9][10][11][12]. Significantly higher titers of IMS than of NHS suggested that lysis of thymocytes could be caused by heterophile antibodies pre sent in IMS in addition to naturally occurring thymocytolysins.…”
Section: Discussionsupporting
confidence: 91%
“…Both NHS and IMS produced lysis of murine thymocytes. This ob servation was in agreement with studies by other investigators, which demonstrated the cytotoxicity of heterologous sera for murine thymo cytes [9][10][11][12]. Significantly higher titers of IMS than of NHS suggested that lysis of thymocytes could be caused by heterophile antibodies pre sent in IMS in addition to naturally occurring thymocytolysins.…”
Section: Discussionsupporting
confidence: 91%
“…The loss of activity of normal rabbit sera after storage confirms previous observations (Terasaki et al 1961) that normal sera cytotoxic to lymphocytes from other species often become inactive after stor-age. Tests with five sera indicated that the loss of activity due to storage at -20" C was not due to anticomplementarity of the sera.…”
Section: Table 2 Coeficients Of Correlation ( R ) Between Lymphocytotsupporting
confidence: 88%
“…Discussion 'That normal rabbit sera contain cytotoxic antibodies directed against human lymphoid cells has been known for several years (Terasaki et al 1961, Herberman 1969, Ferrone et al 1971. Although these antibodies detect antigens on cell surfaces of lymphocytes of normal individuals, they do not appear specific for known H G A antigens.…”
Section: Table 2 Coeficients Of Correlation ( R ) Between Lymphocytotmentioning
confidence: 99%
“…In a very different approach Terasaki and Chamberlain (1962) found that autologous serum from normal rabbits and rats could be toxic in vitro when incubated with their own epidermal cells, though it remains to be determined wivat signiticanco this may have in auto-allergy.…”
Section: Discussionmentioning
confidence: 99%